Basic delivery skills training and the teaching performance of pediatric residents - Santos, Karen Grace O.; Erlyn A. Sana, PhD (Manila National Teacher Training Center for the Health Professions, 2018)
It is known that residents contribute significantly to the education of medical students. Surveys indicate that medical students see their residents as their most important and memorable clinical teachers (Remmen, et al., 2000), (Morrison et al, 2001). However, residency does not include any program capacitating them to teach. This research described the teaching performance of the pediatric residents before and after a basic delivery skills training on set induction, variability, explaining, questioning, and closure. The residents' perception of their teaching task and how they prepared for their teaching activities were also examined. This one group pretest and post-test study was completed in a tertiary hospital in Cavite. Seventeen residents participated in the study. Teaching performance was assessed from five perspectives?self, peers, independent raters, students and consultants and compared before and after a basic delivery skills training. All instruments used were validated by experts and pilot-tested. Inter-rater agreement was done using Kendall?s coefficient of concordance. The data gathered were analyzed by computing the mean, frequencies and percentage distributions. The scores of the participants were compared at different timepoints using repeated analysis of variance followed by Tukey?s multiple comparison test. Data show that majority of the residents had good perception of their teaching task, were regularly engaged in different teaching activities and performed them without any supervision nor training. Factors required in planning a lesson were considered by the residents. Significant difference in teaching performance was noted by all raters before and after the training. There is a significant difference in the teaching performance of pediatric residents before and after the basic delivery skills training. Recommendation: A longitudinal assessment of the resident?s teaching performance and inclusion of the basic delivery skills training in the residency curriculum.
Thesis (Master of Health Professions Education)--University of the Philippines Manila
Panel members: Erlyn A. Sana PhD, Chair/Adviser; Maria Elizabeth M. Grageda PTRP MHPEd, Reader-Critic; Members: Melflor A. Atienza MD MHPEd; Melchor Victor G. Frias IV, MD MscE; Jindra H. Tetangco, MD MHPEd.
Keywords: Intership and residency; Medical education